Arthrodesis for chronic lateral subtalar joint dislocation caused by posterior tibial tendon dysfunction: A case report - Tonogai, Ichiro (Int J Surg Case Rep, 2020)
INTRODUCTION: Adult acquired flatfoot deformity (AAFD) caused by posterior tibial tendon dysfunction (PTTD) can lead to the development of peritalar subluxation (PTS) and much more rarely to lateral subtalar dislocation. PRESENTATION OF CASE: A 75-year-old woman was referred to our hospital with an approximately 15-year history of pain in her right foot without obvious trauma. The lateral shifting foot deformity had worsened in the previous 5 years. On presentation, she had tenderness over the talonavicular joint, and the skin overlying the talar head on the medial foot was taut. Imaging revealed lateral displacement of the calcaneus with simultaneous dislocation of the talonavicular and talocalcaneal joints. We diagnosed lateral subtalar dislocation including the talonavicular and talocalcaneal joints caused by PTTD, which we treated by reduction and fusion of the subtalar joint complex. The foot and ankle were immobilized with a cast for 6 weeks. DISCUSSION: At the 1-year follow-up visit, the patient reported no pain during daily activities, although flatfoot persisted. CONCLUSION: We report a rare case of chronic lateral subtalar dislocation caused by PTTD that was treated by fusion of the talonavicular and talocalcaneal joints.